Enhancing prevention and intervention for youth concurrent mental health and substance use disorders: The Research and Action for Teens study. Issue 1 (26th July 2017) - Henderson, Joanna L.; Brownlie, E. B.; McMain, Shelley; Chaim, Gloria; Wolfe, David A.; Rush, Brian; Boritz, Tali; Beitchman, Joseph H.
Abstract : Background: Concurrent mental health and substance use disorders among youth are associated with functional impairment in developmentally salient domains, yet research on prevention and intervention for this vulnerable population is sparse. This paper describes the rationale and design of the Research and Action for Teens study, an initiative designed to strengthen the evidence base for prevention, screening, treatment and service delivery for youth concurrent mental health and substance use concerns. Methods: Four sub‐studies were developed: (1) a cohort study examining the emergence of mental health and substance use concerns from early to mid‐adolescence; (2) a screening and diagnosis study validating screening tools with a diagnostic interview; (3) a treatment study examining the feasibility and effectiveness of dialectical behaviour therapy skills training interventions for youth and family members; and (4) a systems study implementing cross‐sectoral collaborative networks of youth‐serving agencies using a common screening tool. Results: Multiple stakeholders, including service providers from youth‐serving agencies across sectors, consumer groups and family members participated in an initial consultation, and in the implementation of 4 sub‐studies. Conclusions: Collaboration with community stakeholders across sectors and disciplines throughout the research process is challenging but feasible, and is important for the production of applicable knowledge across the continuum of care.